The Role of Emotional Invalidation and Social Support as a Predictor of Individual Psychological Well-Being in Adulthood - Tricia, Estevania; Fransisca, Fransisca; Caroline Loe, Caroline; Hutapea, Bonar (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Emerging adulthood is when individuals begin to explore and experience many changes in their lives. Social support can improve psychological well-being during this challenging developmental stage. However, research on the influence of emotional invalidation on psychological well-being is still minimal. This study aims to determine the role of emotional invalidation and social support on psychological well-being in early adulthood. This study involved 266 samples consisting of male and female Indonesian citizens aged 18-29 years and applied quantitative methods with purposive sampling techniques. The instruments used for data collection were the Psychological Well-Being Scale, the Multidimensional Scale of Perceived Social Support, and The Perceived Invalidation of Emotion Scale, which were then analyzed using multiple linear regression. The results showed that the role of emotional invalidation and social support on psychological well-being had a high influence with a significant value (p